Waqf as an Instrument of Islamic Governance: Advancing Social Justice, Conflict Resolution, and Sustainable Human Development - Shaaban Idris Abdallah; Adamu Abubakar Muhammad; Ismail Iliyasu Danladi; Abdullah A. Afifi; Ibrahim Isa Bello; Bilyaminu Yusuf (IDRIS Darulfunun Institute, 2026)
Waqf has been among the most stable institutions in Islamic civilization, used in funding diverse services such as education, health care, social assistance, and public services and administration throughout Muslim societies. Despite this rich legacy, scholarship to date has primarily analyzed Waqf from legal, historical, and financial perspectives, with relatively little emphasis on the role of waqf as a form of governance and a tool for achieving sustainable public policy. This article conceptualizes Waqf as a tool for Islamic governance that can be leveraged to advance social justice, support conflict prevention processes, and achieve sustainable human development. Using a qualitative conceptual research design through an integrative review of literature, the study integrates Classical Islamic Political thought, maqasid al-Shariah, Institutional Governance theory, social capital theory, and Sustainable Development discourse into a multidimensional framework of analysis. This yields the Waqf Governance for Sustainable Development (WGSD) Framework. The study demonstrates how ethically governed waqf institutions can operationalize Islamic governance principles into demonstrable outcomes on human development through investments in such areas as education, health care, entrepreneurship, environment conservation, legal services, social security and community mediation. By reframing waqf from a philanthropic endeavor to a governance institution that complements existing states institutions, while addressing issues of social justice, equity, participation and public benefit, the article provides a new dimension to the waqf literature. The study concludes that reforming waqf governance, professionally managing it, leveraging new technologies and integrating waqf policy into broader public policy creates a potent mechanism for inclusive and sustainable development and lasting peace in Muslim societies.